Agile Digital Transformation in Local Government: An Extreme Programming Approach to Public Service Mall Applications - Andini, Dwi Yana Ayu; Rizki, Fahlul; Yulia, Aviv Fitria (Journal of Information System and Informatics, 2025)
The development of the web-based Public Service Mall (MPP) application aims to enhance the quality, efficiency, and accessibility of public services in Pringsewu Regency. Utilizing the Extreme Programming (XP) methodology, which focuses on iterative and collaborative software development, the application follows five main phases: planning, design, coding, testing, and release. Key features of the application include a service search function, a booking code-based queue system, service history tracking, and a user dashboard for seamless interaction. The implementation results demonstrate that the application significantly simplifies access to various public services, reduces physical queues, and improves transparency throughout the service process. System testing confirms that the application operates according to specifications, with a user satisfaction rate of 87% and a notable improvement in service response times. Therefore, this application serves as an effective digital solution that supports the transformation of modern public services, making them more responsive and accessible to the community's needs.